2020
DOI: 10.3746/pnf.2020.25.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamins C and E Co-Supplementation on Serum C-Reactive Protein Level: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Studies assessing the effect of vitamin C and E co-supplementation on levels of circulating C-reactive protein (CRP) show contradictory results. We carried out a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess the effect of vitamin C and E co-supplementation on CRP. A systematic search was carried out using PubMed, Scopus, Ovid, Cochrane, Embase, and the Web of Science without any language or time restriction (until 31 March 2019) to retrieve RCTs that examined the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…In agreement with our data, anti‐inflammatory diets rich in omega‐3 polyunsaturated fatty acids have been proposed as potential treatments for NAFLD because they might enhance hepatic β‐oxidation, decrease endogenous lipid production, and reduce the expression of pro‐inflammatory molecules and oxygen reactive species 31 . Interestingly, the results of a randomised double‐blind placebo‐controlled trial demonstrated that a combined treatment with α‐tocopherol (vitamin E) and vitamin C, which are potent antioxidants with anti‐inflammatory properties, 32 resulted in a significant improvement in the fibrosis scores of participants after 6 months of therapy 33 . Additionally, flavonoids, which act as potent antioxidants, have been shown to exert beneficial effects against NAFLD 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our data, anti‐inflammatory diets rich in omega‐3 polyunsaturated fatty acids have been proposed as potential treatments for NAFLD because they might enhance hepatic β‐oxidation, decrease endogenous lipid production, and reduce the expression of pro‐inflammatory molecules and oxygen reactive species 31 . Interestingly, the results of a randomised double‐blind placebo‐controlled trial demonstrated that a combined treatment with α‐tocopherol (vitamin E) and vitamin C, which are potent antioxidants with anti‐inflammatory properties, 32 resulted in a significant improvement in the fibrosis scores of participants after 6 months of therapy 33 . Additionally, flavonoids, which act as potent antioxidants, have been shown to exert beneficial effects against NAFLD 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study has investigated the pleiotropic effects of ASC on cardiovascular health parameters including blood pressure, lipid profiles, arterial stiffness, and endothelial function [179]. According to a meta-analysis of randomized controlled trials, published in 2015, the oral administration of several natural antioxidant molecules including ASC reduced arterial stiffness and enhanced endothelial function [180]. It has also been demonstrated that supplementation with ASC and tocopherols improved endothelial function, although these effects did not extend to cholesterol or triglyceride metabolism [181] (Table 6).…”
Section: Cardioprotective and Vasculoprotective Properties Of Ascmentioning
confidence: 99%
“…Supplementation of VC and VE has been shown to be useful in preventing bone loss linked to oxidative stress in the elderly (53) . A recent meta-analysis also indicated beneficial effects of VC and VE co-supplementation on serum C-reactive protein (CRP), an important biomarker for predicting diseases, in participants ≥ 30 years of age but not in young subjects (54) . Further, a randomized clinical trial showed that co-administration of VC and VE may improve arterial blood gas parameters and reduce intensive care unit stay in patients with lung contusion (55) .…”
Section: Discussionmentioning
confidence: 99%